ANCA vasculitis expands the spectrum of autoimmune manifestations of activated PI3 kinase δ syndrome - Sood, Amika K.; Francis, Olivia; Schworer, Stephen A.; Johnson, Steven M.; Smith, Benjamin D.; Googe, Paul B.; Wu, Eveline Y. (Frontiers in Pediatrics, 2023)
Activated phosphoinositide 3-kinase δ syndrome (APDS) is a combined immunodeficiency with a broad clinical phenotype, including not only an increased propensity for sinopulmonary and herpesviruses infections but also immune dysregulation, such as benign lymphoproliferation, autoimmunity, and malignancy. Autoimmune complications are increasingly recognized as initial presenting features of immune dysregulation in inborn errors of immunity (IEIs), including APDS, so awareness of the spectrum of autoimmune features inherit within these disorders is critical. We present here a patient vignette to highlight cutaneous antineutrophil cytoplasmic antibody (ANCA) vasculitis as an underrecognized autoimmune manifestation of APDS. The genetic defects underlying APDS result in increased PI3Kδ signaling with aberrant downstream signaling pathways and loss of B- and/or T-cell immunologic tolerance mechanisms, which promote the development of autoimmunity. An understanding of the molecular pathways and mechanisms that lead to immune dysregulation in APDS has allowed for significant advancements in the development of precision-medicine therapeutics, such as leniolisib, to reduce the morbidity and mortality for these patients. Overall, this case and review highlight the need to maintain a high index of suspicion for IEIs, such as APDS, in those presenting with autoimmunity in combination with a dysregulated immune phenotype for prompt diagnosis and targeted intervention.